Successful usage of external beam radiation to myeloma cutaneous lesions in patient with refractory, relapsed multiple myeloma - Chira Ranjan Khadanga; B Saikumar; K Sujatha; Anand Kumar Vaggu; Sambasivaiah Kuraparthy (Indian Journal of Medical and Paediatric Oncology)
Cutaneous myeloma lesions are rare. External beam radiation is effective in inducing remission in cutaneous myeloma lesions.